The Nuklir Iran dalam Neorealisme Defensif: Keamanan Nasional dari hegemoni Amerika Serikat dan Neorealisme Defensif - Mohamad Fuat Najib, Mohamad Fuat Najib (Journal of Integrative International Relations, 2022)
An anarchic international structure system, power is needed by every country to be able to survive. It is also said that the ultimate goal of the state is survival, not achieving power. This means that power is a means, not an end. This is also what Iran does in an international system that is ostensibly controlled by the United States. Iran, with its nuclear possession and development program, is considered a force that can threaten the forces that dominate the region and of course the United States. Iran's nuclear possession in the Middle East will affect other countries around it. In the view of defensive neorealism, Iran in the development of nuclear technology is a form of awareness of safeguarding its national security from the threat of hegemonic forces in the region and of course from the United States which threatens the sovereignty of the Iranian state. Because nuclear is considered as a power possessed by the state besides military and economic power. Sistem struktur internasional yang anarki, power dibutuhkan oleh setiap negara agar mampu bertahan. Dikatakan juga, bahwa tujuan akhir negara adalah bertahan (survival), bukan mencapai power. Dengan maksud bahwa power merupakan sebuah cara, bukan sbuah tujuan. Hal ini juga yang dilakukan Iran dalam sistem internasional yang seolah-olah dikendalikan oleh Amerika Serikat. Iran dengan kepemilikan nuklir dan progam pengembangannya dianggap sebagai kekuatan yang dapat mengancam kekuatan yang menghegemoni kawasan dan tentunya Amerika Serikat. Kepemilikan nuklir Iran di Timur Tengah akan mempengaruhi negara lain yang berada di sekitarnya. Dalam pandangan neorealisme defensif, Iran dalam pengembangan teknologi nuklir merupakan bentuk kesadaran menjaga keamanan nasionalnyaidari ancaman hegemoni kekuatan di kawasan dan tentunya dari Amerika Serikat yang mengancam kedaulatan negara Iran. Sebab nuklir dianggap sebagai power yang dimiliki oleh negara selain kekuatan militer dan ekonomi.